Variation in the Quantity of Elastic Fibres with Degeneration in Canine Cranial Cruciate Ligaments from Labrador Retrievers - Smith, Kinley D.; Hayashi, Kei; Clements, Dylan N.; Clegg, Peter D.; Innes, John F.; Comerford, Eithne J. (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives This study aims to quantify numbers of elastic fibres in cranial cruciate ligaments from a dog breed at high risk of cranial cruciate ligament disease.Methods Macroscopically normal cranial cruciate ligaments were harvested from six Labrador retrievers. Sequential histological sections were assessed for extracellular matrix degeneration (haematoxylin and eosin stain) and elastic fibre staining (Miller’s stain). Elastic fibres were semi-quantified using previously published scoring systems. Each section was scored twice by two observers.Results Increased numbers of elastic fibres were seen with increasing cranial cruciate ligament degeneration (p = 0.001). Labrador retriever cranial cruciate ligaments had lower elastic fibre staining when compared with previous published findings in the racing greyhound.Clinical Significance The cranial cruciate ligaments from a dog breed at high risk of cranial cruciate ligament disease vary in the quantity of elastic fibres in association with ligament degeneration. Breed variation in the quantity of elastic fibres may reflect differing risk of cranial cruciate ligament disease.
Keywords: dogs; cruciate ligament disease; elastic fibres